Mercado de tierras en la Comunidad Campesina de Miluchaca – Sapallanga 2019 - Huamán Pérez, Francisca (2021)
The research entitled: Land market in the Campesino Community of Miluchaca - Sapallanga 2019, aimed to identify the factors that facilitate the expansion of the land market in the Campesino Community of Miluchaca - Sapallanga The general method that guided the research is the scientist The type of research is basic, qualitative research approach, level of descriptive research, hermeneutical phenomenological research design, the techniques were documentary analysis, semi-structured interview and observation. Finding that the expansion of the land market is due to the demand of land from immigrants for the construction of housing mainly, for this reason the owners in this case the bidders first sanitized the properties and immediately sell these lands at prices that the market imposes. Finally, it is concluded that the land market in the Campesino Community of Miluchaca has been expanding rapidly due to the demand of immigrants and the owners' offer due to economic needs. These lands to enter the market had to be cleared by legitimizing private property in favor of the possessors.